Global strategies for domestic firms in emerging economies in a world of multinationals: toward a model - Li, Mingfang (2002)
An issue little studied in the field of global strategic management is that of the strategies that local companies in emerging economies must adopt to effectively face the challenges of a globalized economy replete with multinationals. This article explores key dimensions of local business strategies, reviews the main elements of business strategies, corporate strategy, global orientation and the mixture of competitive approaches. It then integrates these dimensions and strategic elements into a conceptual framework that identifies viable types of strategies so that local companies in emerging economies can compete effectively with their powerful and resource-rich counterparts. The research considers previous contributions, limitations and future lines of research.